Characterisation of Ganoderma boninense Isolates from Sarawak, the Causal Agent of Basal Stem Rot in Elaeis guineensis - Mei Lieng, Lo (Springer, 2023)
Malaysia’s oil palm industry has been threatened by basal stem rot (BSR), a difficult-to-cure disease caused by Ganoderma boninense. This disease causes yield and palm losses by shortening the economic life cycle of the oil palm. However, there is a critical knowledge gap on G. boninense aggressiveness in the Sarawak region, and their metabolic profile remain poorly explored. Therefore, this study employed various approaches to differentiate G. boninense isolates aggressiveness, including measurements of seedlings vegetative growth, chlorophyll content, photosynthetic rate, disease incidence (DI), disease severity index (DSI), and the in vitro growth rate of the isolates on different media. Subsequently, the metabolic profiles of the most and least aggressive G. boninense isolates in this study were characterised using BIOLOG Phenotype Microarray (PM). Six G. boninense isolates sampled from Balingian, Daro, and Kuala Igan, namely BLSM5B, DR51B, BLSM5A, BLSM4A, IGKI3, and DR56, were artificially inoculated onto two-month-old oil palm seedlings. Based on the aggressiveness parameters employed in this study, the isolates were categorised into three groups: highly aggressive (BLSM5B), moderately aggressive (DR51B, BLSM5A, BLSM4A, and IGKI3), and less aggressive (DR56). The measurements of chlorophyll content and photosynthetic rates proved to be highly sensitive to G. boninense infection. Notably, the bole size of the seedlings remained unaffected throughout the study. Spearman's rank correlation revealed that chlorophyll content and photosynthetic rate display a negative correlation with the DSI, whereas in vitro growth rate on malt extract agar (MEA) showed a positive correlation with DSI. Additionally, most G. boninense reisolated in this study exhibited faster growth than those from the original culture stock on MEA. Isolate BLSM5B stands out as a promising candidate for future studies related to BSR disease management and control strategies. In terms of substrate utilisation, isolate BLSM5B demonstrated the ability to utilize a wide range of substrates (carbon (65.26%), nitrogen (72.63%), phosphorus (88.14%), and sulphur (74.29%) compared to the less aggressive isolate, DR56 (4.73%, 57.89%, 81.36%, 62.86%, and 64.89%, respectively). Additionally, isolate BLSM5B exhibited a robust biosynthetic pathway (93.62%) and growth on various pH conditions (81.91%) compared to isolate DR56 (21.28% and 64.89, respectively). However, isolate DR56B is more efficient in the utilisation of peptide nitrogen (72.34%) and the growth on various osmolytes condition (60%) in comparison to isolate BLSM5B (70.57% and 46.32%, respectively). Both isolates were unable to metabolize sodium benzoate at a pH of 5.2 (20–200 mM), preferred Ala-Asp (nitrogen source) and Met-His, Thr-Arg, Gly-Asn, and Thr-Gln (peptide nitrogen source), and a pH of 4.5 in the presence of 5-hydroxy tryptophan. In addition, the comparisons of substrate utilisation between isolates BLSM5B and DR56 showed a significant difference in their utilisation in certain substrates. These findings offering valuable insights for the development of new ways to manage BSR, highlighting the importance of identifying specific nutrients or conditions that support the growth of G. boninense, thereby enabling more precise and effective control measures. Among the disease confirmation techniques employed in this study, molecular detection of fungal DNA isolated from infected tissue demonstrated the highest recovery percentage. The amplification of fungal DNA extracted from the infected tissue using the ITS3/GanET primers without subsequent sequencing, proved to be reliable for disease detection. Incorporating molecular identification is essential to improve the precision and reliability of disease confirmation whenever a culture-based approach is required.